P0099CALCINEURIN INHIBITION, BUT NOT DEHYDRATION, IN RATS MIMICS HUMAN RENAL HISTOPATHOLOGY OF PATIENTS WITH CHRONIC INTERSTITIAL NEPHRITIS IN AGRICULTURAL COMMUNITIES (CINAC). (6th June 2020) - Schreurs, Gerd; Nast, Cynthia; Maudsley, Stuart; D'Haese, Patrick; De Broe, Marc; Vervaet, Benjamin
Abstract: Background and Aims: CINAC patients present a newly discovered constellation of proximal tubular lysosomal lesions which is also observed in patients experiencing calcineurin inhibitor (CNI) nephrotoxicity, suggesting that CINAC is a toxin-induced nephropathy involving calcineurin inhibition. An alternate hypothesis advocates chronic heat stress/dehydration as the major etiological factor for CINAC. Here, we evaluated in rats to what extent heat stress/dehydration versus CNI exposure reflects proximal tubular CINAC histopathology. Method: Wistar rats were divided in 3 groups. Group 1 (n=6) was given water ad libitum (control group). Group 2 (n=8) was water deprived for 10 hours per 24h, 5 days/week and were placed in an incubator (37°C) for 30 min/hr of water deprivation. Group 3 (n=8) underwent daily oral gavage with cyclosporine (50mg/kg body weight). Animals were weighed daily and urine was collected at day 3, 17 and 28. After 28 days, rats were sacrificed. Kidneys were collected for light (LM) and electron microscopic (EM) histopathological analysis as well as for cortical renal tissue proteomics. Results: Cyclosporine rats developed focal cortical lesions mimicking those of CINAC patients: i.e. atrophic proximal tubuli with thickened basement membranes and associated tubulo-interstitial fibrosis, PASM staining demonstrating enlarged argyrophyllic granules in the affected proximal tubuli, LAMP1 immunofluorescent staining identifying a subset of these granules as lysosomes, and EM confirming the presence of enlarged lysosomes, some dysmorphic approaching CINAC lysosomes. In dehydrated rats, confirmed by urinary osmolality and fluctuating body weight associated with water deprivation, none of the cyclosporine features were observed. Proteomic analysis confirmed cellular toxicity by cyclosporine, whereas the dehydration group lacked any markers of such. Conclusion: The histopathological analogy between CNI nephrotoxicity in rats and humans and CINAC suggests a toxicological etiology for CINAC. In rats, dehydration/heat stress alone does not lead to the constellation of proximal tubular lesions as observed in CINAC patients.